Prestasi Akademik dan Perilaku Komunikasi Remaja Pengguna Game Online Free Fire (Studi Kasus di Desa Hijrah, Kecamatan Lape) - Aminuddin, Aminuddin; Rakhmatullah, Vivin Nila (YASIN, 2024)
This research aims to determine the Academic Achievement and Communication Behavior of Adolescent Free Fire Online Game Users in Hijrah Village, Lape District. The research method used is qualitative descriptive with a research focus on case studies. This case study is a type of research that tries to understand a situation in depth and provide meaning. The type of case study used in this research is a situation analysis case study of a particular event or event. The data collection technique used is through documentation, in-depth interviews with informants to determine the Academic Achievement and Communication Behavior of Teenagers who use the Free Fire Online Game in Hijrah Village, Lape District. These findings provide valuable images and insights for parents, educators and researchers to understand more deeply about academic achievement and communication behavior.